Database on detected stellar occultations by small outer Solar System objects - Braga-Ribas, F.; Crispim, A.; Vieira-Martins, R.; Sicardy, B.; Ortiz, J. L.; Assafin, M.; Camargo, J. I.B.; Desmars, J.; Lecacheux, J.; Santos-Sanz, P.; Duffard, R.; Benedetti-Rossi, G.; et al. (IOP Publishing, 2019)
Observation of stellar occultation by objects of the Solar System is a powerful technique that allows measurements of size and shape of the small bodies with accuracies in the order of the kilometre. In addition, the occultation star probes the surroundings of the object, allowing the study of putative rings/debris or atmosphere around it. Since 2009, more than 60 events by trans-Neptunian and Centaur objects have been detected, involving more than 34 different bodies. Some remarkable results were achieved, such as the discovery of rings around Chariklo and Haumea, or the high albedo of Eris, the lack of global atmosphere around Makemake and the discovery of the double shape of 2014 MU69, among others. After the release of Gaia catalogues, predictions became more accurate, leading to an increasing number of successful observations of occultation events. To keep track of the results achieved with this technique, we created a database to gather all the detected events worldwide. The database is presented as an electronic table (http://occultations.ct.utfpr.edu.br/), where the main information obtained from any occultation by small outer solar system objects are listed. The structure and term definitions used in the database are presented here, as well as some simple statistics that can be done with the available results.